Analysis of the technology for controlling digital data transmission channels with compression in computer systems - Dovhij, V.V.; Hryha, V.M.; Dzundza, B.S.; Svyd, I.V.; Terletsky, A.I.; Pavlyuk, M.F. (Radiotekhnika, 2025)
When transmitting digital data, various types of errors may occur, including in the data address, and accordingly, there is a need to regulate the data transfer rate. In this case, simple synchronization technology is no longer enough, and it is necessary to use a data link control protocol that would provide data flow control, error detection and protection against the latter. For the effective use of high-speed communication lines, signal compression is used, which allows several transmission sources to use the high bandwidth of the channel. The paper analyzes the technology for controlling digital data transmission channels with compression in computer systems. Two forms of control are considered: frequency-division multiplexing (FDM) and time-division multiplexing (TDM). It is shown that sufficient data transfer speed and bandwidth, low price and the ability to use when operating from autonomous power sources make xDSL technology relevant, especially as a backup Internet access channel.